Serological, cultural and molecular evidence of Brucella melitensis infection in goats in Al Jabal Al Akhdar, Sultanate of Oman. Issue 3 (23rd May 2018) - ElTahir, Yasmin; Al Toobi, Al Ghalya; Al‐Marzooqi, Waleed; Mahgoub, Osman; Jay, Maryne; Corde, Yannick; Al Lawati, Hadi; Bose, Shekar; Al Hamrashdi, Abeer; Al Kharousi, Kaadhia; Al‐Saqri, Nasseb; Al Busaidi, Rudaina; et al.
Abstract: Brucellosis, one of the most common zoonotic diseases and has significant public health and economic importance worldwide. Few studies and reports have been performed to estimate the true prevalence of animal brucellosis in the Sultanate of Oman; however, no incidence of the disease was previously reported in Al Jabal Al Akhdar. The purpose of this study was to investigate the prevalence of brucellosis in goats in eight villages in Al Jebal Al Akhdar, Sultanate of Oman, namely: Al Aqaieb, Al Helailat, Al Ghilayil, Hail Al Hedap, Da'an Al Hamra, Shnoot, Al Qasha'e and Al Sarah, Al Jabal Al Akhdar in the Sultanate of Oman. In this study we used different diagnostic serological tests, namely, RBT, I‐ELISA and CFT to study the prevalence of Brucella infection in goats in Al Jabal Al Akhdar. Statistical analysis using Kappa statistics was used to compare the performance of the serological tests. Biochemical tests and species‐specific Multiplex PCR were used to identify the brucella species involved in the infection. A structured questionnaire and Chi‐square (x 2 ) statistical analysis was used to identify related brucellosis risk factors. This study is the first to reveal brucellosis infection in goats in eight villages in Al Jebal Al Akhdar, Sultanate of Oman, namely: Al Aqaieb, Al Helailat, Al Ghilayil, Hail Al Hedap, Da'an Al Hamra, Shnoot, Al Qasha'e and Al Sarah, with an overall seroprevalence of 11.1%. The study also compared the performance of three different serological tests, namely, RBT, I‐ELISA and CFT. Statistical analysis using Kappa statistics showed that the degree of agreement was best seen between RBT and CFT (96%), followed by RBT, I‐ ELISA (91.4%) and CFT and I‐ ELISA (89.2%). Biochemical tests and species‐specific Multiplex PCR showed the typical profile for B. melitensis . A structured questionnaire and Chi‐square (x 2 ) statistical analysis indicated that the presence of abortion is the major risk factor for the prevalence of brucellosis, whereas age and sex were not significant factors in the tested animals. Besides, poor knowledge about brucellosis, consumption of unpasteurized milk or milk products, free trade of animals and the introduction of new animal breeds to herds were all contributing risk factors to the prevalence of brucellosis. The prevalence of human brucellosis obtained verbally from pastoralists gave an insight that brucellosis could pose a public health hazard, especially in those high‐risk groups, mainly the pastoralists in the study area. Because of their constant and increasing interaction with their animals, pastoralists could be at a high risk of occupational infection. Abstract : Impacts: This study is the first to reveal that brucellosis is prevalent in goats in Al Jabal Al Akhdar, Sultanate of Oman with an overall prevalence of 11.1%. Statistical analysis using Kappa statistics showed the degree of agreement between the performances of three different serological tests was best seen between RBT and CFT (96%) followed by RBT and I‐ ELISA 91.4%, and CFT and I‐ ELISA 89.2%. The use of Bruce‐ladder multiplex PCR allowed us to detect, for the first time, B. melitensis in goats in Al Jabal Al Akhdar.